Genetic evaluation of Addison's disease in the Portuguese Water Dog. - Oberbauer, AM.; Bell, JS.; Belanger, JM.; Famula, TR. (2016)
Background: Addison's disease, also known as hypoadrenocorticism, has been reported in many individual dogs, although some breeds exhibit a greater incidence than the population as a whole. Addison's is presumed to be an autoimmune mediated hereditary defect but the mode of inheritance remains unclear. In particular, the heritability and mode of inheritance have not been defined for the Portuguese Water Dog although Addison's is known to be prevalent in the breed.; Springer Open.